2021
DOI: 10.1186/s12983-021-00386-0
|View full text |Cite
|
Sign up to set email alerts
|

Cranial morphology of captive mammals: a meta-analysis

Abstract: Background Captive facilities such as zoos are uniquely instrumental in conservation efforts. To fulfill their potential as bastions for conservation, zoos must preserve captive populations as appropriate proxies for their wild conspecifics; doing so will help to promote successful reintroduction efforts. Morphological changes within captive populations may be detrimental to the fitness of individual animals because these changes can influence functionality; thus, it is imperative to understand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 115 publications
1
15
0
Order By: Relevance
“…The shape differences observed here between captive and wild M. fuscata (when overall shape and the symmetric components are analysed) suggest that captivity has exerted pressures on development. In addition, even accounting for the limitations of our analysis, morphological differences between captive and wild mammal species have long been recognised [30], thus suggesting that captivity does have an impact on the developing morphology. Whether captivity (or, in general, environmental stress) tends to affect only the overall shape, skeletal symmetry, or both is still highly uncertain, although it has been suggested that FA and phenotypic variance arise from at least partially overlapping processes [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The shape differences observed here between captive and wild M. fuscata (when overall shape and the symmetric components are analysed) suggest that captivity has exerted pressures on development. In addition, even accounting for the limitations of our analysis, morphological differences between captive and wild mammal species have long been recognised [30], thus suggesting that captivity does have an impact on the developing morphology. Whether captivity (or, in general, environmental stress) tends to affect only the overall shape, skeletal symmetry, or both is still highly uncertain, although it has been suggested that FA and phenotypic variance arise from at least partially overlapping processes [21].…”
Section: Discussionmentioning
confidence: 99%
“…Much evidence exists about the impact of captivity on animal behaviour [27,28]. However, how living in a captive environment can influence an individual or a group's morphology is still unclear [29,30]. Fishes raised in captivity have shown significantly higher levels of fluctuating asymmetry on different morphological traits, some of remarkable functional importance, such as the length of the pectoral and ventral fins [31].…”
mentioning
confidence: 99%
“…In addition to nutritional influences, the mechanical properties of the diet and functional demands of feeding habits might play a role in the plastic response of the cranial and mandibular morphology and associated masticatory muscles (Groves 1966 ; Herring and Lakars 1981 ; Lieberman et al 2004 ; O'Regan and Kitchener 2005 ; Paschetta et al 2010 ; Hartstone-Rose et al 2014 ; Cornette et al 2015 ; Fabre et al 2018 ; Siciliano-Martina et al 2021 ). Specifically for primates, it has been found that squirrel monkeys ( Saimiri sciureus ) fed a soft diet exhibit a narrower muzzle than specimens which have been fed a harder diet (Corruccini and Beecher 1982 ).…”
Section: Discussionmentioning
confidence: 99%
“…Osteological material from many of these Japanese macaque populations has been sampled through decades and documented meticulously in institutional and museum collections. Thus, these Japanese macaque populations present an ideal case for studying variation in cranial and mandibular shape and size as well as the pace of this change as a response to different levels of human–animal interactions, despite a recent meta-analysis finding only minor morphological changes in primates due to captivity (Siciliano-Martina et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Some endangered species have been maintained in these facilities until they are able to be reintroduced to the wild (Frankham, 2008; Conde et al ., 2011; Willoughby et al ., 2015). However, the environment, available food and stressors that captive populations experience are largely different from those of wild populations and may influence animal behavior, physiology and morphology (O’Regan & Kitchener, 2005; Siciliano‐Martina, Light & Lawing, 2021 a , b ), handicapping success in the wild where optimal functionality is imperative (Wisely et al ., 2005; Frankham, 2008; Courtney Jones, Munn & Bryne, 2018).…”
Section: Introductionmentioning
confidence: 99%